2015
DOI: 10.1007/s13132-015-0330-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Business Firms, Knowledge Flows and Intra-Network Open Innovations

Abstract: The increasing competition in the marketplace has led firms to change their innovation patterns to a more open system according to which they rely on networks to manage knowledge resources and innovate. The so-called open innovation paradigm has been developed by taking single-business firms and external networks as cornerstones of the standard model. However, in the case of multi-business firms, the role of internal networks has been neglected. Business units within multi-business corporations have the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 71 publications
0
11
0
1
Order By: Relevance
“…A qualitative approach might be applied to this empirical analysis to investigate in depth the way in which the digitalisation supports the implementation of really open and collaborative frameworks inside and outside firms. Finally, showing the relevant relationships of four proxies with the use of ICTs, we believe that the use of ICTs could improve SMEs' innovativeness as stated by (Llamas and Belk 2013): SMEs firm boundaries (Villasalero 2015(Villasalero , 2014bD'Ambrosio et al 2017) have become key to competitiveness, learning and innovation. Accordingly, the results also confirmed that there is a positive relationship between the use of ICTs and knowledge sharing activities (H 2 ).…”
Section: Discussion Implications Final Remarks and Future Lines Of mentioning
confidence: 64%
“…A qualitative approach might be applied to this empirical analysis to investigate in depth the way in which the digitalisation supports the implementation of really open and collaborative frameworks inside and outside firms. Finally, showing the relevant relationships of four proxies with the use of ICTs, we believe that the use of ICTs could improve SMEs' innovativeness as stated by (Llamas and Belk 2013): SMEs firm boundaries (Villasalero 2015(Villasalero , 2014bD'Ambrosio et al 2017) have become key to competitiveness, learning and innovation. Accordingly, the results also confirmed that there is a positive relationship between the use of ICTs and knowledge sharing activities (H 2 ).…”
Section: Discussion Implications Final Remarks and Future Lines Of mentioning
confidence: 64%
“…Hence, to understand firms' innovation activities, we must consider not only internal R&D efforts, but also external sources of knowledge and firms' search activities (Villasalero 2015). Accordingly, we investigate the role of the search channels represented by various kinds of collaboration partners, including universities, public institutions and other private firms, and the scope of these collaborations-local versus global relationshipsthat firms use to search for innovative opportunities.…”
Section: The Role Of External Sources Of Knowledgementioning
confidence: 99%
“…Our study confirms cooperative managerial solutions already identified in the open innovation literature for outside-in knowledge from startups into multiunit organizations. 48 But our case study shows that in addition to the cooperative aspect, respect for and leveraging the competition is also needed in this context 49 as shown by the literature on the management of coopetition. The empirical managerial solutions identified to overcome the business rivalry and unlock the corporate-startup collaboration on digitalization transformation program-namely, the anonymization of the data, the addition of a champion level in charge of ensuring the collaboration and competition, the incentive systems (resources), and the temporal disconnect-are managerial tools already identified in the literature on managing internal coopetition and digital transformation, but to our knowledge, they have never been connected to the open innovation problems.…”
Section: Resultsmentioning
confidence: 84%